ANALYSIS OF CHANNELS AND MARKETING MIX OF FLYING FISH EGGS IN POPO VILLAGE, GALESONG SELATAN DISTRICT, TAKALAR REGENCY - Nurjannah; Marhawati, Muhammad Jufri (Adisam Publisher, 2025)
This study aims to determine the pattern of marketing channels and the marketing mix of flying fish eggs in Popo Village, South Galesong District, Takalar Regency. The research was conducted using a descriptive, empirical and qualitative research approach. The method used consists of inductive reasoning. This research was conducted in Popo Village, South Galesong District, Takalar Regency. which is one of the coastal areas where most of the people work as Patorani fishermen (fish egg catchers). Meanwhile, to determine respondents using simple random sampling. The results showed that there were 3 marketing channel patterns for flying fish eggs in Popo Village, South Galesong District, Takalar Regency where the most important marketing pattern profitable for fishermen was in channel II pattern, namely fishermen - collectors - wholesalers. The margin obtained by each marketing channel pattern is the same in pattern 1 and 3, which is IDR 200,000. and the pattern of marketing channels 2 obtains a margin of 150,000. And the marketing mix is one of the marketing strategies to communicate information widely, present goods and services, encourage consumers to buy and even create personal preferences for these products.